Tumor Long-interspersed Nucleotide Element-1 Methylation Level and Immune Response to Esophageal Cancer. Issue 6 (December 2020) - Kosumi, Keisuke; Baba, Yoshifumi; Okadome, Kazuo; Yagi, Taisuke; Kiyozumi, Yuki; Yoshida, Naoya; Watanabe, Masayuki; Baba, Hideo
Abstract : Objective: To examine the relationship between tumor long-interspersed nucleotide element-1 (LINE-1) methylation level and immune response to esophageal cancer. Background: Evidence points to a correlation between the abundance of immune cells and a favorable prognosis in esophageal cancer patients. Accumulating evidence indicates a critical role of tumor LINE-1 hypomethylation in the aggressive behavior of esophageal cancer, which in turn leads to an unfavorable prognosis. Methods: Utilizing a nonbiased database of 292 resected esophageal cancers, we measured tumor LINE-1 methylation level by pyrosequencing assay, and examined the relationship between LINE-1 methylation and the density of T cells (CD8 and FOXP3) and the lymphocytic reaction patterns (follicle lymphocytic reaction, peritumoral lymphocytic reaction, stromal lymphocytic reaction, and tumor-infiltrating lymphocytes) in esophageal carcinoma tissue. Results: LINE-1 hypomethylation was associated with male gender and advanced stage cancer ( P = 0.03 and P = 0.048, respectively). Tumor LINE-1 methylation level was significantly positively associated with peritumoral lymphocytic reaction ( P = 0.004), but not with others. Compared with LINE-1 hypermethylation group, LINE-1 hypomethylation group showed much lower level of peritumoral lymphocytic reaction (univariable odds ratio 0.32, 95% confidence interval 0.16–0.64, P = 0.002). In multivariable model to control for potential confounders including disease stage, the similar finding was observed (multivariable odds ratio 0.31, 95% confidence interval 0.14–0.66, P = 0.004). Conclusions: Tumor LINE-1 hypomethylation level is associated with a diminished peritumoral lymphocytic reaction, providing impetus for further investigations on potential interactive roles of tumor LINE-1 hypomethylation and host immunity in esophageal cancer development. Abstract : Supplemental Digital Content is available in the text